ANALISIS HERMENEUTIKA GADAMER TERHADAP LARANGAN BERBUAT KERUSAKAN QS. AL-A‘RAF 56 DALAM TAFSIR AL-AZHAR KARYA BUYA HAMKA - Muhammad Wafa; Anggita Sofianti (Yayasan Baitul Hikmah al-Zain, 2026)
This study aims to describe how Hans-Georg Gadamer's hermeneutic approach is held in the interpretation of the Qur'an, especially in Buya Hamka's interpretation of QS. al-A'raf: 56. The researcher uses a qualitative-descriptive method with text analysis techniques and a hermeneutic approach. The researcher found that Buya Hamka in his interpretation, interpreted the prohibition of causing damage after repairs not ecologically, but Buya Hamka chose to interpret it morally and spiritually. In Gadamer's hermeneutic analysis, the researcher saw that Buya Hamka when interpreting the verse seemed to be influenced by history, both educational background, ideology and the reality that occurred in his life, thus creating a pre-understanding (prejudices) when interpreting. After the pre-understanding, Buya Hamka was seen when interpreting the verse by dialoguing between Buya Hamka's horizon as an interpreter and the horizon of the Qur'an text. Buya Hamka's historical influence is very visible by the influence of his father as a modernist Islamic figure in Indonesia. Apart from that, Buya Hamka's rejection of the concept of traditional Sufism which tends to hate the world and must be avoided, also the social context surrounding it tends to forget the moral aspect so that there is mutual hostility between each other.